Immunohistochemical FAP expression reflects 68Ga-FAPI PET imaging properties of low- and high-grade intraductal papillary mucinous neoplasms and pancreatic ductal adenocarcinoma - Spektor, Anna-Maria; Gutjahr, Ewgenija; Lang, Matthias; Glatting, Frederik M.; Hackert, Thilo; Pausch, Thomas; Tjaden, Christin; Schreckenberger, Mathias; Haberkorn, Uwe; Röhrich, Manuel (Journal of nuclear medicine, 2024)
Pancreatic intraductal papillary mucinous neoplasms (IPMNs) are grossly visible (typically > 5 mm) intraductal epithelial neoplasms of mucin-producing cells, arising in the main pancreatic duct or its branches. According to the current 2-tiered grading scheme, these lesions are categorized as having either low-grade (LG) dysplasia, which has a benign prognosis, or high-grade (HG) dysplasia, which formally represents a carcinoma in situ and thus can transform to pancreatic ductal adenocarcinoma (PDAC). Because both entities require different treatments according to their risk of becoming malignant, a precise pretherapeutic diagnostic differentiation is inevitable for adequate patient management. Recently, our group has demonstrated that 68Ga-fibroblast activation protein (FAP) inhibitor (FAPI) PET/CT shows great potential for the differentiation of LG IPMNs, HG IPMNs, and PDAC according to marked differences in signal intensity and tracer dynamics. The purpose of this study was to biologically validate FAP as a target for PET imaging by analyzing immunohistochemical FAP expression in LG IPMNs, HG IPMNs, and PDAC and comparing with SUV and time to peak (TTP) measured in our prior study. Methods: To evaluate the correlation of the expression level of FAP and α-smooth muscle actin (αSMA) in neoplasm-associated stroma depending on the degree of dysplasia in IPMNs, 98 patients with a diagnosis of LG IPMN, HG IPMN, PDAC with associated HG IPMN, or PDAC who underwent pancreatic surgery at the University Hospital Heidelberg between 2017 and 2023 were identified using the database of the Institute of Pathology, University Hospital Heidelberg. In a reevaluation of hematoxylin- and eosin-stained tissue sections of formalin-fixed and paraffin-embedded resection material from the archive, which was originally generated for histopathologic routine diagnostics, a regrading of IPMNs was performed by a pathologist according to the current 2-tiered grading scheme, consequently eliminating the former diagnosis of "IPMN with intermediate-grade dysplasia." For each case, semithin tissue sections of 3 paraffin blocks containing neoplasm were immunohistologically stained with antibodies directed against FAP and αSMA. In a masked approach, a semiquantitative analysis of the immunohistochemically stained slides was finally performed by a pathologist by adapting the immunoreactive score (IRS) and human epidermal growth factor receptor 2 (Her2)/neu score to determine the intensity and percentage of FAP- and αSMA-positive cells. Afterward, the IRS of 14 patients who underwent 68Ga-FAPI-74 PET/CT in our previous study was compared with their SUVmax, SUVmean, and TTP for result validation. Results: From 98 patients, 294 specimens (3 replicates per patient) were immunohistochemically stained for FAP and αSMA. Twenty-three patients had LG IPMNs, 11 had HG IPMNs, 10 had HG IPMNs plus PDAC, and 54 had PDAC. The tumor stroma was in all cases variably positive for FAP. The staining intensity, percentage of FAP-positive stroma, IRS, and Her2/neu score increased with higher malignancy. αSMA expression could be shown in normal pancreatic stroma as well as within peri- and intraneoplastic desmoplastic reaction. No homogeneous increase in intensity, percentage, IRS, and Her2/neu score with higher malignancy was observed for αSMA. The comparison of the mean IRS of FAP with the mean SUVmax, SUVmean, and TTP of 68Ga-GAPI-74 PET/CT showed a matching value increasing with higher malignancy in 68Ga-FAPI-74 PET imaging and immunohistochemical FAP expression. Conclusion: The immunohistochemical staining of IPMNs and PDAC validates FAP as a biology-based stromal target for in vivo imaging. Increasing expression of FAP in lesions with a higher degree of malignancy matches the expectation of a stronger FAP expression in PDAC and HG IPMNs than in LG IPMNs and corroborates our previous findings of higher SUVs and a longer TTP in PDAC and HG IPMNs than in LG IPMNs.